The Relationship Between Areas of Occupation and Severity of Depression, Anxiety, and Stress in Parkinson's Disease - Omid Farajpour Khazai; Ebrahim Pishyareh; Mahdi Rassafiani; Enayatollah Bakhshi; Mohsen Poursadeqiyan (University of Social Welfare and Rehabilitation Sciences, 2019)
Objective Parkinson's Disease (PD) is a neurodegenerative progressive condition with a number of nonmotor symptoms such as depression, anxiety, and stress. These have the most debilitating characteristics and increase the severity and progression of the disease and often reduce functional ability in the sufferers. For this reason, they may, over time, lose their daily living activities skills (basic and instrumental) and social participation. The current study investigated the relationship between the areas of occupation and severity of depression, anxiety, and stress in PD. Materials & Methods In this cross-sectional (descriptive-analytical) study, 91 PD patients referring to rehabilitation centers and hospitals in Tehran City, Iran, were selected through convenience sampling method. After obtaining approval from the University of Social Welfare and Rehabilitation, we referred to the centers and hospitals; if managers of the centers accepted to cooperate with the research team, the study was conducted in accordance with the inclusion criteria in that center. The Assessment of Life Habits (Life-H) test was used to evaluate the areas of occupation and the Depression, Anxiety and Stress Scale (DASS-21) was applied to assess depression, anxiety, and stress. Life-H test subscales were categorized by the occupational therapists of the university, based on the classification of the areas of occupation. The obtained data were analyzed using Pearson's correlation coefficient, Spearman's rank correlation coefficient, multiple regression analysis, focal correlation, Independent Samples t-test and Mann-Whitney U test in SPSS. Results The collected results indicated a reverse and significant correlation between the level of Activities of Daily Living (ADL)'s participation and depression. Additionally, the correlation between the levels of participation in education and leisure was inverse and significant in terms of anxiety and stress. The correlation coefficient between the areas of occupation and depression was as r=0.362, P=0.06; between the areas of occupation and anxiety was as r=0.49, P=0.001; and between the areas of occupation and stress was as r=0.5,  P=0.001. There was a significant correlation between the different areas of occupation and stress and anxiety; however, the correlation between the areas of occupation and depression was not significant. Focal correlations between the areas of occupation and nonmotor symptoms (depression, anxiety, and stress) were equal to r=0.55, P=0.05 and significant. Conclusion There was a significant relationship between the areas of occupation and the incidence of nonmotor symptoms (depression, anxiety, and stress) in people with PD. Therefore, we can facilitate the direction of rehabilitation and occupational therapy's settings for clinicians, by identifying the areas of occupation that are more affected by the disease; this may help to provide disease-related facilities and may have economic benefits for caregivers of PD patients.